Optical and mechanical excitation thermography for impact response in basalt-carbon hybrid fiber-reinforced composite laminates - Zhang, Hai; Sfarra, Stefano; Sarasini, Fabrizio; Ibarra-Castanedo, Clemente; Perilli, Stefano; Fernandes, Henrique; Duan, Yuxia; Peeters, Jeroen; Avdelidis, Nicolas P.; Maldague, Xavier P. (IEEE, 2017)
In this paper, optical and mechanical excitation thermography were used to investigate basalt fiber reinforced polymer (BFRP), carbon fiber reinforced polymer (CFRP) and basalt-carbon fiber hybrid specimens subjected to impact loading. Interestingly, two different hybrid structures including sandwich-like and intercalated stacking sequence were used. Pulsed phase thermography (PPT), principal component thermography (PCT) and partial least squares thermography (PLST) were used to process the thermographic data. X-ray computed tomography (CT) was used for validation. In addition, signal-to-noise ratio (SNR) analysis was used as a means of quantitatively comparing the thermographic results. Of particular interest, the depth information linked to Loadings in PLST was estimated for the first time. Finally, a reference was provided for taking advantage of different hybrids in view of special industrial applications.
Keywords: Infrared thermography; Nondestructive testing; Hybrid composite; SNR analysis